Pengaruh Kemasaman, Suhu, dan Cahaya terhadap Golovinomyces sordidus Penyebab Penyakit Embun Tepung pada Plantago major - Dini Florina; Dyah Manohara; Dono Wahyuno (Jurnal Fitopatologi Indonesia, 2014)
Unidentified powdery mildew was found on leaves of a medicinal plant, Plantago major in Indonesia. The present studies were aimed to identify the causal fungal species of powdery mildew of  P. major and study the effect of acidity, temperature and light on the causal fungus. Identification was conducted by observing morphological characteristics of the fungus scraped from diseased leaves under light microscope. The infection process was observed by staining the inoculated leaves followed observation under light microscope. Conidia were suspended in various pH solutions to examine effect of pH on conidial germination and hyphal length. For testing effects of temperature on conidial germination and hyphal length, conidial suspensions were dropped onto glass slides then incubated in temperature ranges from 20–35 °C, the germinating conidia and length of the existing hypha were counted and measured 24 hours later. With the same method as above the glass slides were incubated in 25 °C either in the dark or exposed under illuminated white light tube (400 Lux) for study effect of light on conidial germination. The causal fungus was identified as Golovinomyces sordidus (syn. Erysiphe sordida) with its anamorph state as Oidium. The germinating conidia penetrate directly into leaf tissue within 24 hours. The optimal conditions for the conidia to germinate are pH between 4 and 7, temperature between 25 °C and 30 °C, and dark condition.